Tocotrienols in Different Parts of Wild Hypericum perforatum L. Populations in Poland - Paweł Górnaś; Edyta Symoniuk (Molecules)
St. John’s wort (Hypericum perforatum L.) is a well-known medicinal plant widely used in phytotherapy due to its abundant secondary metabolites with bioactive properties. Research on tocochromanols conducted in nine populations of St. John’s wort using reverse-phase high performance liquid chromatography with fluorescent light detector (RP-HPLC-FLD) has provided new insights into their diverse composition in different aerial parts of the plant. Flower buds displayed the most diverse tocochromanol profile, while stems contained the lowest levels of these compounds. In most of the examined tissues, δ-T3 was the predominant tocochromanol (34–69%), except in leaves, where α-T dominated. The highest concentration of total tocotrienols was recorded in flower buds (48.5–74.1 mg/100 g dry weight), with δ-T3 (56%) and α-T3 (38%) as the dominant compounds. The highest δ-T3 content was found in unripe seed pods (29.6–45.1 mg/100 g dw). Principal Component Analysis (PCA) revealed distinct differences in tocochromanol composition among the aerial parts of H. perforatum. The findings highlight that H. perforatum has higher potential applications in the food, pharmaceutical, and medical industries than previously assumed, due to its relatively high content of tocotrienols, mainly δ-T3, in different plant organs.